Enhancing the enzymatic digestibility of oil palm biomass using supercritical carbon dioxide-based pretreatment towards biorefinery application - Saima, Sohni; Rokiah, Hashim; Hafiz, Nidaullah; Othman, Sulaiman; Leh, Cheu Peng; Junidah, Lamaming; Arai, Takamitsu; Kosugi, Akihiko (Elsevier B.V, 2020)
In realizing the vast potential of lignocellulosic biomass residues generated by oil palm industry under the regime of ‘one-size-fits-all’ biorefinery concept, supercritical carbon dioxide (SC-CO2) technology offers great promise. Herein, we demonstrated a new eco-friendly pretreatment of oil palm trunk biomass based on SC-CO2 under controlled conditions of pressure (25, 35 and 45 MPa), temperature (80, 100 and 120 ◦C) and moisture content (0, 20, 40 and 60 %), and investigated their effect on enzymatic hydrolysis yields of the pretreated fractions. During pretreatment, biomass sample reacted with hot water in SC-CO2 which led to high diffusivities, promoting its disruption and xylan solubilisation as supported by various characterization techniques. This study illustrates that hydrolysis yields are influenced by process parameters, particularly the moisture content played a crucial role in the biomass disruption. The SC-CO2 pretreatment resulted in enhanced digestibility for all the pretreated fractions compared to the untreated biomass.